Motivations for sustained participation in crowdsourcing: The role of talk in a citizen science case study - Corey Brian Jackson; Carsten Østerlund; Gabriel Mugar; Kevin Crowston; Katie DeVries Hassman (Proceedings of the Forty-eighth Hawai'i International Conference on System Sciences (HICSS-48), 2015)
The paper explores the motivations of volunteers in a large crowd sourcing project and contributes to our understanding of the motivational factors that lead to deeper engagement beyond initial participation. Drawing on the theory of legitimate peripheral participation (LPP) and the literature on motivation in crowd sourcing, we analyze interview and trace data from a large citizen science project. The analyses identify ways in which the technical features of the projects may serve as motivational factors leading participants towards sustained participation. The results suggest volunteers first engage in activities to support knowledge acquisition and later share knowledge with other volunteers and finally increase participation in Talk through a punctuated process of role discovery.